Researching power, elites and leadership - Williams, Christopher R. (Sage, 2012)
"This exciting new text consolidates the how's and why's of researching powerful people. Written by a leading authority in the field, this book introduces the reader to a significant area of methodology, and provides a research-based contribution to elite and leadership studies. It offers a truly international perspective that will appeal to those studying and working with elites in a variety of contexts. Useful features include: A variety of case studies and examples linked to over 1000 sources and resources; Extensive use of figures throughout the text to illustrate key points; Templates and models for planning and presentations The book promotes a practical future-oriented approach to support and inspire academic, professional and civil society researchers at all levels. It introduces new research frameworks and facilitates critical techniques through Critical Process Analysis. This is a must-have resource and an excellent new addition to the field of elite and leadership studies."--Publisher's website.